Cervicothoracic Spinal Epidural Empyema Causing Tetraparesis: Case Report and Literature Review - Cembraneli, Pedro Nogarotto; Cavalcante, Julia Brasileiro de Faria; Cembraneli, Italo Nogarotto; Cavalcante, Renata Brasileiro de Faria; Cavalcante, José Edison da Silva; Lopes, Leonardo Taveira; Xavier, Marcos Daniel; Cardoso, Alessandro Fonseca; Cardoso, Chrystiano Fonseca (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Spinal Epidural Empyema (SEE) is a rare and severe central nervous system infection characterized by pus in the epidural space of the spine, often caused by bacteria such as Staphylococcus aureus. Although its incidence has increased in recent decades, diagnosis remains challenging. Risk factors include advanced age, invasive surgeries, injectable drug use, and central venous catheters. The clinical presentation typically includes spinal pain, fever, and focal neurological deficits. Diagnosis is confirmed by contrast-enhanced magnetic resonance imaging (MRI). Case Presentation: This report describes a 41-year-old female with a history of urinary tract infection who developed tetraparesis, cervicalgia, and fever. MRI revealed an extensive fluid collection in the epidural space from C5 to T6, with spinal cord compression. Urgent surgical intervention was required for decompression and purulent drainage, with Staphylococcus aureus identified as the causative pathogen. Following two weeks of intravenous antibiotics, the patient showed significant recovery of strength in both upper and lower limbs. Conclusion: Early intervention with surgical decompression and appropriate antibiotics is crucial to prevent severe neurological sequelae. Raising awareness and achieving a prompt diagnosis are key to improving patient outcomes and quality of life.